2017
DOI: 10.1089/jwh.2016.5957
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related 30-Day and Long-Term Mortality in Acute Myocardial Infarction Patients Treated with Percutaneous Coronary Intervention

Abstract: Older age, comorbidities, worse clinical presentation, and adjunctive pharmacotherapy rather than sex may explain the higher mortality rate in women with MI undergoing PCI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…1 ). This gender differences also reflect in 30-day mortality [OR 0.64, 95% CI 0.61–0.66, P = .04, I 2 = 40%; 19 studies (n = 523,304)], [ 2 4 , 7 , 8 , 13 17 , 23 , 25 , 26 , 33 36 , 42 , 53 ] 1-year mortality [OR 0.67, 95% CI 0.60–0.75, P < .001, I 2 = 73%; 20 studies (n = 590,590)] [ 8 , 10 , 13 , 15 17 , 20 , 25 , 26 , 28 , 30 , 33 , 35 , 36 , 38 , 43 , 44 , 53 55 ] and >2-years mortality [OR 0.71, 95% CI 0.63–0.79, P = .005, I 2 = 57%; 14 studies (n = 43,096)] [ 4 6 , 18 , 19 , 23 , 29 , 31 , 34 , 36 , 40 , 43 , 52 , 56 ] (Figs. 2 – 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). This gender differences also reflect in 30-day mortality [OR 0.64, 95% CI 0.61–0.66, P = .04, I 2 = 40%; 19 studies (n = 523,304)], [ 2 4 , 7 , 8 , 13 17 , 23 , 25 , 26 , 33 36 , 42 , 53 ] 1-year mortality [OR 0.67, 95% CI 0.60–0.75, P < .001, I 2 = 73%; 20 studies (n = 590,590)] [ 8 , 10 , 13 , 15 17 , 20 , 25 , 26 , 28 , 30 , 33 , 35 , 36 , 38 , 43 , 44 , 53 55 ] and >2-years mortality [OR 0.71, 95% CI 0.63–0.79, P = .005, I 2 = 57%; 14 studies (n = 43,096)] [ 4 6 , 18 , 19 , 23 , 29 , 31 , 34 , 36 , 40 , 43 , 52 , 56 ] (Figs. 2 – 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…[ 2 44 ] Some studies have showed persistent gender difference in outcomes after adjusting multivariate factors, [ 2 , 5 , 7 , 9 , 10 , 13 , 15 , 18 , 20 25 , 28 , 30 33 , 35 39 , 41 43 ] while other studies also demonstrated that gender was not an independent factor for patient's outcome. [ 3 , 4 , 11 , 12 , 14 , 17 , 19 , 26 , 27 , 29 , 34 , 40 , 44 ] Although previous meta-analysis has demonstrated the effect of gender on response to PCI, which not involved major adverse cardiovascular events (MACE) and revascularization, and the follow-up period was also comparatively short. [ 45 48 ] Therefore, this meta-analysis was designed to determine the gender difference in patients with coronary artery disease after PCI, and provide evidence for the development of the guideline.…”
Section: Introductionmentioning
confidence: 99%
“…The cause of sex‐specific excess risk is postulated to be multifactorial. Women undergoing PCI have atypical clinical presentation, are frequently delayed in diagnosis and treatment, are older age, and have larger comorbidity burden 1‐9 . However, even after adjustment of these procedural and clinical characteristics, the results are inconsistent among clinical studies 7,10 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, significant differences regarding clinical profile, management and prognosis according to gender have been previously described in patients with cardiovascular disease [ 6 9 ]. Importantly a significantly lower adherence to current recommendations has been consistently described in other clinical scenarios, especially in patients with Acute Coronary Syndromes (ACS) [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%